2003
DOI: 10.1002/food.200390077
|View full text |Cite
|
Sign up to set email alerts
|

Chemical and biochemical changes in prickly pears with different ripening behaviour

Abstract: Chemical and biochemical changes were studied in ripening prickly pears from three Opuntia morphospecies with different ripening behaviour: Naranjona (O. ficus-indica), Blanca Cristalina (Opuntia sp.), and Charola (O. streptacantha), of early, intermediate, and late ripening, respectively. At fullyripe stage (commercial maturity), Blanca Cristalina showed the biggest fruits, the hardest texture, and its pulp had the highest protein content. There were no significant differences among morphospecies in pH or tot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
5
3

Year Published

2006
2006
2022
2022

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(12 citation statements)
references
References 20 publications
(16 reference statements)
4
5
3
Order By: Relevance
“…ese findings were in agreement with those of Méndez and Batista [32,33] who reported that Ca values were clearly higher than 1.5-3.5% DW. Our data for iron and zinc fell well within the range described in the same literature but higher than those for prickly pear fruit, pulp, and juice [29,32,34]. e mineral quantities detected in CF could make it a good supplement for commercial foods.…”
Section: Physicochemical Properties Of Cladode Floursupporting
confidence: 87%
“…ese findings were in agreement with those of Méndez and Batista [32,33] who reported that Ca values were clearly higher than 1.5-3.5% DW. Our data for iron and zinc fell well within the range described in the same literature but higher than those for prickly pear fruit, pulp, and juice [29,32,34]. e mineral quantities detected in CF could make it a good supplement for commercial foods.…”
Section: Physicochemical Properties Of Cladode Floursupporting
confidence: 87%
“…Protein (%) content of PPJs ranged from 1.22 to 1.74 g/100 g and it was significantly (p < 0.05) higher in "Bastardoni" fruits in comparison to "Agostani". Such results were higher than those reported by Gurrieri et al, Dehbi et al and El-Gharras et al [21][22][23] and were comparable to those found by Díaz Medina et al, Sáenz and Sepúlveda and Silos-Espino et al [24][25][26]. These differences may be attributed both to the pedoclimatic conditions at which prickly pears were grown and to the different variety.…”
Section: Evaluation Of Physical and Chemical Propertiessupporting
confidence: 76%
“…When the dietary fiber contents of xoconostle cv. Cuaresmeño peel and skin were compared to those of the edible part of prickly pear (pulp) (4.2% to 7.8%, DWB) (Silos‐Espino and others 2003; Hernández‐Pérez and others 2005), xoconostle shows to be an outstanding source of fiber. Dietary fiber may contribute in the prevention of chronical diseases such as diabetes, cancer and cardiovascular illnesses (Roehrig 1988).…”
Section: Resultsmentioning
confidence: 99%